(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Annotation This article delves into the concept of social distance and its implications for intercultural interactions, offering strategies for effectively managing culture clashes. It discusses the factors contributing to social distance, such as cultural norms and values, and explores the challenges and conflicts that arise when individuals from different cultural backgrounds encounter differences. Through practical tips and insights, the article provides guidance on fostering cultural awareness, practicing effective communication, and promoting cross-cultural understanding.